Hybrid UV-Ozone-Treated rGO-PEDOT:PSS as an Efficient Hole Transport Material in Inverted Planar Perovskite Solar Cells - Wang, Shuying; Huang, Xiaona; Sun, Haoxuan; Wu, Chunyang (Nanoscale research letters, 2017)
Inverted planar perovskite solar cells (PSCs), which are regarded as promising devices for new generation of photovoltaic systems, show many advantages, such as low-temperature film formation, low-cost fabrication, and smaller hysteresis compared with those of traditional n-i-p PSCs. As an important carrier transport layer in PSCs, the hole transport layer (HTL) considerably affects the device performance. Therefore, HTL modification becomes one of the most critical issues in improving the performance of PSCs. In this paper, we report an effective and environmentally friendly UV-ozone treatment method to enhance the hydrophilia of reduced graphene oxide (rGO) with its excellent electrical performance. The treated rGO was applied to doped poly(3,4-ethylenedioxythiophene) poly(styrene-sulfonate) (PEDOT:PSS) as HTL material of PSCs. Consequently, the performance of rGO/PEDOT:PSS-doped PSCs was improved significantly, with power conversion efficiency (PCE) of 10.7%, J sc of 16.75 mA/cm 2 , V oc of 0.87 V, and FF of 75%. The PCE of this doped PSCs was 27% higher than that of the PSCs with pristine PEDOT:PSS as HTL. This performance was attributed to the excellent surface morphology and optimized hole mobility of the solution-processable rGO-modified PEDOT:PSS.